Evaluating the knowledge sharing efforts in the chief minister's department, Sarawak - Ngo, Jane Siok Ing (Universiti Malaysia Sarawak, (UNIMAS), 2011)
fhis study aims to evaluate the knowledge sharing efforts in the Chief Minister's Department, Sarawak, Malaysia. The objective of this study is to determine the relationship between individual dimension, organizational dimension and technological dimension and knowledge sharing efforts in this organization and also which the most dominant dimension among the thre~ The respondents for this research are employees that are currently serving in the Chief Minister's Depart, Sarawak from Management and Professional, and Support Group 1. The findings are based on the results of 143 self-administered questionnaire feedback carried out in May 2011. The results revealed that there is significant, positively moderate degree of relationship between these three dimensions and knowledge sharing efforts in this organization. Based on the multiple regression analysis, technological dimension was deemed most dominant towards knowledge sharing efforts.